Children and their curriculum : the perspectives of primary and elementary school children - Pollard, Andrew, 1949-; Thiessen, Dennis; Filer, Ann (Falmer Press, 1997)
The aim of this text is to encourage educators and researchers in recognizing pupil perspectives. Its central argument is that understanding some of the disparity between ""curriculum as intended"" and ""curriculum as experienced"" will increase the quality of school life and improve learning.